2022
DOI: 10.1136/bmjopen-2021-058205
|View full text |Cite
|
Sign up to set email alerts
|

Trends in bacterial sepsis incidence and mortality in France between 2015 and 2019 based on National Health Data System (Système National des données de Santé (SNDS)): a retrospective observational study

Abstract: ObjectiveThis study aims to provide a case definition of sepsis of presumed bacterial aetiology based on 10th revision of the International Classification of Diseases (ICD-10) codes, to assess trends in sepsis incidence and mortality between 2015 and 2019 in France, and to describe the characteristics of affected patients and hospital stays.DesignNationwide, population-based, retrospective observational study.SettingMetropolitan France between 2015 and 2019.ParticipantsBetween 2015 and 2019, 1 224 433 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
1
10
2
Order By: Relevance
“…Further, we found that implicit sepsis patients had the same risk as explicit sepsis patients. This is in contrast to a nationwide study based on ICD-10 codes, and a study investigating mortality trends comparing clinical versus claims data, and found that explicit sepsis had a higher in-hospital mortality 31,27 . For comparison, some of the diverging results can be explained by ICD-10 code selection and search strategies, where they included other combinations of ICD-10 codes to identify implicit sepsis and searched in a lower number of secondary diagnoses to combine infection and organ dysfunction.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…Further, we found that implicit sepsis patients had the same risk as explicit sepsis patients. This is in contrast to a nationwide study based on ICD-10 codes, and a study investigating mortality trends comparing clinical versus claims data, and found that explicit sepsis had a higher in-hospital mortality 31,27 . For comparison, some of the diverging results can be explained by ICD-10 code selection and search strategies, where they included other combinations of ICD-10 codes to identify implicit sepsis and searched in a lower number of secondary diagnoses to combine infection and organ dysfunction.…”
Section: Discussioncontrasting
confidence: 97%
“…The meta-analysis by Stevenssons and colleagues (2014) found an annual decrease of 3.0% in 28-day mortality 28 , while the meta-analysis by Luhr et al (2019) found an annual decrease of 0.42% in 28-day mortality, which was more pronounced in studies with a mean age ≥65 years. Our approach of using administrative databases to calculate mortality trends in sepsis patients is common 2,5,7,30,31 , but not without controversy 10,32 . The decline in mortality rates are often attributed to the Will-Rogers phenomenon, which explains reduced mortality as a consequence of including a larger proportion of less severely ill sepsis patients due to increased sepsis awareness 33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study consisted of a secondary data analysis of a cohort of all patients with bacterial infections and registered in the anonymized French National Hospital Discharge Database (Programme de Médicalisation des Systèmes d'Information: PMSI) and outpatient health care consumption (Données de Consommation Inter-Régimes: DCIR) issued from the French health care database (Système National des Données de Santé: SNDS) (see Additional file 1 : eMethods) [ 27 , 28 ]. Therefore, only cases of sepsis of presumed bacterial etiology (referred to herein as sepsis) were considered.…”
Section: Methodsmentioning
confidence: 99%
“…The selection in the French medico-administrative database was based on a list of ICD-10 codes, organ dysfunction and ICU admission (see Additional file 1 : eMethods and eTable 1). More details about the selection can be found in our previous study [ 27 ]. Only hospital stays in an acute-care facility (MSO: medicine surgery and obstetrics) were considered.…”
Section: Methodsmentioning
confidence: 99%